Long-term permanent plot observations of vegetation dynamics in Budongo, a Ugandan rain forest - Sheil, Douglas; Jennings, S.; Savill, P. (2000)
Species composition and turnover in a series of' permanent sample plots established during the 1930s and 1940s in Budongo, a semi-deciduous Ugandan forest, are reported. The plots were established as part of' a sequence first used to describe forest succession, five of' which have been maintained. One plot provides 53 years of data from old-growth pristine forest, another established in wooded grassland at the forest edge is now closed high forest. Evaluation of the remaining three plots is complicated by silvicultural interventions in the 1950s. Forty species have been added since the first evaluations and 188 tree species (over 80%, of' Budongo's forest tree flora) have now been recorded. In the original plot series there is an increasing proportion of shade-tolerant species with development, and large stems appearing to 'lag behind' smaller stems in this respect. The time series data are less consistent, and while the proportion of shade-tolerant stems increased through time in the pristine forest plot, the proportion of shade-tolerant species declined. Most species have a higher recruitment than mortality rate and stem numbers increased in all plots. This is most pronounced in the putatively 'early successional’ plot. Stem size structure has changed within the plots, with an increased proportion of smaller stems. Species show different rates of turnover and these vary, from plot to plot and period to period. It is estimated that some tree species will live longer than 500 years after reaching 10 cm diameter (bh), and 1000 years is possible. The importance of large trees in determining forest dynamics is illustrated by the finding that death of only seven stems in the pristine forest plot contributed over 60% of net basal area losses over the 53 years. Many patterns observed were not predicted, showing the importance of long-term studies.